Hubungan Anemia Dengan Kejadian Ketuban Pecah Dini Pada Ibu Hamil Di RSUD Embung Fatimah - Asfri Sri Rahmadeni; Nahrul Hayat (Jurnal Keperawatan Muhammadiyah, 2022)
PROM (premature rupture of membranes) is still an issue in obstetrics. PROM can be caused by a variety of reasons, one of which being anemia, which affects 12-70 percent of pregnant women in Indonesia. The goal of this study at Embung Fatimah Hospital was to see if there was a link between anemia and the rate of early rupture of membranes in pregnant women. An analytic observational method with a cross sectional design was used in this investigation. A total of 69 mothers were included in the study. According to the study's findings, there were 34 maternity mothers who suffered from anemia (49.3 percent ). There were 38 women who experienced early rupture of membranes during their pregnancy (55.1 percent ). The total number of The P-value for the chi square test was 0.000 0.05, according to the results of the investigation. It is intended that moms will pay greater attention to their health and check in with health services, and that health care providers will provide more education and other high-quality health services to pregnant women to reduce difficulties.